STRATEGI PEMANUFAKTURAN SEBAGAI VARIABEL PEMEDIASI ANTARA STRATEGI KOMPETITIF DIFERENSIASI DAN KINERJA PERUSAHAAN - Soni Kurniawan, Ignatius (Widya Warta, 2011)
This research adopted part of research framework of Amoako-Gyampah and Acquaah (2008). It aimed to examine whether or not the manufacturing strategy mediated a relationship between differentiation competitive strategies and firm performance. The sample of the research was manufacture firms located in Jababeka Industrial Estate, West Java. The sample was taken applying a non-probability method with a purposive sampling technique. The data collecting was carried out using mail survey technique with questionnaires sent via post and e-mail survey technique. The data were analyzed making use of path analysis technique. The result of the analysis indicated that the differentiation competitive strategies influenced four dimensions of manufacturing strategy, but the strategies did not influence the performance of the firms directly. The finding showed that among the four dimensions of the strategies, only quality influenced the performance of the firms. Based on the result, a conclusion can be drawn that the differentiation competitive strategies influenced the performance of the firms through quality.